A new reality: Exploring continuance intention to use mobile augmented reality for entertainment purposes. (November 2021) - Hung, Shiu-Wan; Chang, Che-Wei; Ma, Yu-Chen
Abstract: Augmented Reality (AR) is a technology that combines virtual objects with the real world. In recent years, the rapid development of smartphones has provided a suitable environment for AR technology. This study aims to explore the continuance intention to utilize AR mobile entertainment applications, using the decomposed theory of planned behavior. The research hypotheses were verified using structural equation modeling, which revealed that: (1) telepresence, perceived mobility, perceived enjoyment, and perceived connectedness exert a positive effect on users' attitude toward AR mobile apps; nostalgia is the only factor not to do so; (2) perceived critical mass has a significant positive impact on subjective norms, whereas peer influence does not; (3) self-efficacy has a significant positive influence on perceived behavioral control but facilitating conditions does not; and (4) users' attitude, subjective norms, and perceived behavioral control all have significant positive impacts on users' intention to continue to use the technology. Highlights: This study explores the continuance intention to utilize AR mobile entertainment applications. We integrated the DTPB to construct a SEM analysis model. We verified the critical factors for AR usage. Perceived critical mass significantly influences the intention to continue using. We provided an integrated theoretical insight into consumers' continued use.